CEO turnover and corporate performance relationship in pre- and post- IFRS period: evidence from Turkey - Durukan, Banu; Ozkan, Serdar; Dalkilic, Fatih (Journal of Business Economics and Management, 2012)
This study investigates CEO turnover and corporate performance relationship as a measure of the effectiveness of a corporate governance system. The impact of different financial accounting regimes on the turnover/performance relationship is also analyzed. If systems replace poorly performing managers, they are considered as not ineffective. The results provide evidence that corporate governance systems with poor governance characteristics may not be ineffective, due to the existence of alternative governance mechanisms. The disciplinary CEO turnover is found to be more strongly associated with corporate performance compared to voluntary CEO turnover, whereas in the IFRS subsample the relationship is stronger with contemporaneous performance measures.